Salidroside induced repair of myocardial infarction through Nrf2/HO-1 - Yanbo Fan; Wei Wang; Liqun Tian; Jie Yin (Universidade de São Paulo, 2022)
Abstract Salidroside (SAL) has been confirmed to have some protective effects against inflammatory injury. However, little information was established as to the mechanism of these protective effects. To this effect, we designed this study to explore the protective effects and mechanisms of SAL against myocardial infarction (MI). A rat MI model was established and divided into five groups (n = 6): sham, MI, MI+SAL, MI+ LY294002 (PI3K inhibitor), and MI+SAL+ LY294002. The cardiac function and histological pathology were analyzed with a color Doppler ultrasonic diagnostic instrument. Anti-oxidative enzyme activities and the production of inflammatory media were assayed by biochemical kits and ELISA. MI size and fibrosis were assayed by Masson's trichrome staining while Bax/Bcl-2 and PI3K/Akt/Nrf2/HO-1 were assayed by Western blotting and immunofluorescence. The results showed that SAL significantly improved the left ventricle ejection fraction and fractional shortening, decreased the MI size and fibrosis, inhibited apoptosis and promoted blood vessel formation. SAL promoted anti-oxidative and anti-inflammatory abilities. Moreover, SAL enhanced PI3K/ Akt/Nrf2/HO-1 expression. To this effect, we designed this study suggested that SAL induced repair of MI via PI3K/A kt/ Nrf2/HO-1.